Question Number 102698 by bramlex last updated on 10/Jul/20

Answered by bramlex last updated on 10/Jul/20

∫f(x) dx = h(x) ⇒f(x) = h′(x)  5+x^2 f(x) = 16x^3 −((15)/2)(√x)   x^2 f(x)=16x^3 −((15(√x))/2)−5  f(x)=16x−((15)/(2x(√x)))−(5/x^2 )=16x−((15)/2)x^(−3/2) −5x^(−2)   f ′(x)=16+((45)/(4x^2 (√x)))+((10)/x^(−3) )

Answered by floor(10²Eta[1]) last updated on 10/Jul/20

5+x^2 f(x)=16x^3 −((15(√x))/2)  f(x)=16x−((15)/2)x^(−3/2) −5x^(−2)   f′(x)=16+((45)/4)x^(−5/2) +10x^(−3)   f′(−2)=16+((45)/4)×(1/(√((−2)^5 )))+10×(1/((−2)^3 ))  =((59)/4)+((45)/(16i(√2)))

Commented bybramlex last updated on 10/Jul/20

⌣•⌣•⌣